Технологічний аудит в контексті підвищення ефективності систем управління виробництв аміаку - Бабіченко, Анатолій Костянтинович; Красніков, Ігор Леонідович; Бабіченко, Юлія Анатоліївна; Вельма, Володимир Іванович (Полтавська державна аграрна академія, ПП "Технологічний Центр", 2014)
У статті представлені результати досліджень відділення моноетаноламінової очистки агрегату синтезу аміаку серії АМ-1360 із застосуванням методу технологічного аудиту. Експериментально-статистичною обробкою даних отримані числові характеристики точності і стабільності процесу, що дозволило визначити напрями вдосконалення системи управління, реалізація якої забезпечує стабілізацію температурного режиму відділення і зниження витратних норм енергоносіїв.

In the context of the general problem of increasing energy efficiency of domestic large-scale ammonia synthesis plants of the AM-1360 series, the problem of improving the hardware-technological design and control system of monoethanolamine purification unit is solved in the paper. The possibilities of solving this problem by the technology audit method are considered. Operating conditions of monoethanolamine purification unit are analyzed. Using static processing of experimental data on the unit operation, the main indicators, characterizing the process accuracy factor, setting accuracy and stability were determined that has allowed to determine the cause of instability and displacement of temperature flow formation centers from normative values towards their increase. Based on these indicators, technical solutions on improving technological design and control system are developed, which have provided, due to their implementation, decrease in temperature mode of material flows of monoethanolamine solution and carbon dioxide, emerging from the regenerator in the form of gas-vapor mixture. Implementing technical solutions has allowed to reduce the corrosion rate of the regenerator pipe still and reduce consumption rates of monoethanolamine, vapor in the regenerator, demineralized water for air cooling and energy units at the carbon dioxide cooling node. Based on the research results, the technology audit algorithm is proposed.
Technology audit in the context of increasing the efficiency of ammonia production control systems
Keywords: виробництво аміаку; хімічна промисловість; аміачне виробництво; моноетанламінова очистка; технологічний аудит; енергозбереження; ammonia production; monoetanolamine purification; technology audit; control system; energy-saving